Penerapan Metode SWOT Blue Ocean Strategy pada PT. Mandala Multifinance Tbk. Cabang Meulaboh - Rusdi; Natasya, Kezia Salsia (Medan Resource Center, 2022)
This article aims to discuss the application of the swot blue ocean strategy method at PT. Mandala Multifinance Tbk. Meulaboh Branch. This study uses a qualitative descriptive research method that tries to find out what types and models of strategies are used by Mandala Multifinance in an effort to increase the company's sales. This type of data collection technique is carried out by means of observation and interviews. From this research, we find out what types and models of strategies are being used by Mandala Multifinance to increase sales of its products. The analysis is carried out using four-step work such as the elimination process, so there are no factors that need to be eliminated. For the step of reducing it is also concluded that there are no factors that need to be reduced. For steps to improve, the company needs to increase product innovation and promotion. For the step of creating, the company needs to create several factors such as accepting design suggestions from customers and being able to provide unique forms of service as well as creating new types of multi-finance products that are in great demand by customers.